The Effect Of Squat Training Using Resistance Bands On Leg Strength In Beginner Swimmer - Desi Ratnasari; A. Heri Riswanto; Hikrawati Hikrawati; Rachmat Hidayat (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of Squat Exercises using resistance bands on leg strength in swimming athletes at the Garuda Laut Palopo Club. The method used in this study is a one-group pretest-posttest experiment design with a quantitative approach. Based on the results of the data analysis that has been done, The number of research subjects is 12. With an average (mean) pre-test value of 66.25 and a post-test value of 81.08. Std deviation pre-test 2,864 and post-test 3,232. The minimum value of the pre-test is 60, and the post-test is 75. Moreover, the normality test shows that the pre-test and post-test data have a value of ρ (Sig.) > 0.05, so the variables are normally distributed. Because the data is normally distributed, it can be continued. Then a t-test was conducted with the results obtained, namely sig, 0.000 <0.05. This can be seen from the sig value, 0.000 <0.05, which means Ho is rejected. Thus, it can be concluded that squat training using resistance bands significantly affects leg strength in beginner swimming.